ANALYSIS OF NIST METHODS ON FACEBOOK MESSENGER FOR FORENSIC EVIDENCE - Suhardjono,; Arman Syah Putra,; Nurul Aisyah,; V.H. Valentino, (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to find evidence from forensics on Facebook Messenger using the NIST method. With this method, it can be described one by one the stages that will be used to prove the chat as forensic evidence. The method used in this research is to use the literature review method and perform an analysis of Facebook Messenger which will be used as a test site in this research so that it can be proven that there is forensic evidence. The problem raised in this research is how to find the problem of forensic evidence on Facebook Messenger so that it can be used as evidence to prove a crime. The purpose of this study is to prove that using the NIST method, you can find forensic evidence against Facebook Messenger so that it can be used as evidence at a later date.